Novel reinforcement behavior in nanofilled natural rubber (NR) / butadiene-acrylonitrile rubber (NBR) blends: Filling-polymer network and supernanosphere. (9th January 2020) - Han, Tinghui; Nagarajan, Selvaraj; Zhao, Hongying; Sun, Chong; Wen, Shipeng; Zhao, Suhe; Zhao, Shugao; Zhang, Liqun
Abstract: It is worthy to understand the reinforcement of nanoparticle in rubber blends in application prospect because of its dispersion and distribution. The dielectric and mechanical methods were used to study the reinforcement impact of the carbon black (CB) in NR/NBR blends, based on the percolation and reinforcement theories. Results indicated that the CB aggregates had dispersed in NBR phase and the reinforcement effect was dependent on both CB concentration and the rubber blend ratio. It has been observed that the CB particles diffused and filling in the NBR reinforcement network at 50:50 ratio of NR/NBR blend, CB particles assembled as supernanosphere at 70:30 ratio and CB particles wrapped/covered supernanosphere at 90:10 ratio. The highest elongation at break was observed in 90:10 ratio of NR/NBR. The new observations are conducive to providing guidelines for producing high mechanical performance and low conductivity percolation threshold elastomers via a maturely industrial method for a wide range of application. Graphical abstract: Image 103059 Highlights: It is very clear that the carbon black (CB) is mostly distributed in the NBR phase in all NR/NBR compositions. The dispersion of CB aggregates is affected by CB content and the rubber blend ratio, forming different reinforcing structures, and the reinforcement is evidently enhanced compared with single rubber composition. High mechanical performance and low conductivity percolation threshold elastomers can be made by tuning CB and NBR content.